2007
DOI: 10.1017/s1740925x08000082
|View full text |Cite
|
Sign up to set email alerts
|

Reduced EGFR signaling in progenitor cells of the adult subventricular zone attenuates oligodendrogenesis after demyelination

Abstract: Neural progenitor cells expressing the NG2 proteoglycan are found in different regions of the adult mammalian brain, where they display distinct morphologies and proliferative rates. In the developing postnatal and adult mouse, NG2 + cells represent a major cell population of the subventricular zone (SVZ). NG2 + cells divide in the anterior and lateral region of the SVZ, and are stimulated to proliferate and migrate out of the SVZ by focal demyelination of the corpus callosum (CC). Many NG2 + cells are labeled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 54 publications
4
59
0
1
Order By: Relevance
“…1d,e). We have previously demonstrated that in the 2′,3′-cyclic-nucleotide 3′-phosphodiesterase (CNP)-EGFP mouse, in which all developmental stages of the OL lineage can be visualized based on EGFP expression, the majority of proliferating EGFP + cells under normal or pathological conditions are OPCs1435. Therefore, we wanted to determine whether Sirt1 expression was upregulated in proliferative OPCs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1d,e). We have previously demonstrated that in the 2′,3′-cyclic-nucleotide 3′-phosphodiesterase (CNP)-EGFP mouse, in which all developmental stages of the OL lineage can be visualized based on EGFP expression, the majority of proliferating EGFP + cells under normal or pathological conditions are OPCs1435. Therefore, we wanted to determine whether Sirt1 expression was upregulated in proliferative OPCs.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether Sirt1 plays a specific role in OPC proliferation in neonatal white matter, we used a model of focal (lysolecithin-induced) demyelination of adult white matter35. We analysed white matter lesions at 7 days after demyelination, that is, at a time point when OPC proliferation is maximal35.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, mutant mice defective in TGFα or EGFR expression present reduced numbers of astrocytes at the adult age (Kornblum et al 1998 ;Sibilia et al 1998 ;Weickert and Blum 1995 ) and enhanced astrocyte apoptosis (Wagner et al 2006 ). Like astrocytes, NSC and NPC (including the NG2 progenitor population) remain responsive to EGFR signaling from development to adult ages, responding notably to EGFR activation by enhanced proliferation (Aguirre and Gallo 2007 ;Craig et al 1996 ;Doetsch et al 2002 ; ( a ) Schematic representation of the signaling pathways most frequently deregulated in human glioma. Genes whose activation or inhibition is associated with glioma are depicted in rose and blue, respectively.…”
Section: Common Signalling Pathways Controlling Gliosis and Glioma Dementioning
confidence: 99%
“…EGF was increased in the injured region of the cortex to which SVZ cells migrated after cortical aspiration [202], while cerebral ischemia produced a larger number of EGFR-positive NPCs in the SVZ [20,203]. Following nigrostriatal denervation, TGFα infusion into the striatum induced emigration of SVZ cells [204,205], while reduction of EGFR signaling in progenitors expressing neuron glial antigen 2 decreased their proliferative and migratory response to demyelination [206]. Interestingly, Ninomiya et al [203] showed that in the ischemic brain there was an increase in the number of NPCs but a decrease in neuroblasts during EGF infusion into the parenchyma; however, 6 days after the discontinuation of EGF delivery, there was a substantial rise in the number of neuroblasts in the SVZ and striatum.…”
Section: Injury-induced Factors Mediating Redirected Migration To Dammentioning
confidence: 99%